2021
DOI: 10.3390/healthcare9111550
|View full text |Cite
|
Sign up to set email alerts
|

Who Cares What the Doctor Feels: The Responsibility of Health Politics for Burnout in the Pandemic

Abstract: Modern health has become a defining facet of contemporary life managed by health policy. The COVID-19 pandemic has significantly affected mental health, resulting in stress and anxiety in doctors’ professional and private life. Since the beginning of the pandemic, doctors have been facing chronic stress, which was reported to the hospital managers and health-care agencies, but nothing was done in the practice to protect them. Although doctors are trained to stay emotionally restrained, a large number of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Nevertheless, it is concerning that all health professionals in our study reported positive scores for the presence of Burnout Syndrome, which aligns with the findings by Rahmati (2019) who identified psychological effects, anxiety, depression, and chronic stress as consequences of prolonged stress exposure [66]. Institutional policy can be an aggravating factor and contribute to chronic stress [67].…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, it is concerning that all health professionals in our study reported positive scores for the presence of Burnout Syndrome, which aligns with the findings by Rahmati (2019) who identified psychological effects, anxiety, depression, and chronic stress as consequences of prolonged stress exposure [66]. Institutional policy can be an aggravating factor and contribute to chronic stress [67].…”
Section: Discussionsupporting
confidence: 88%
“…Healthcare organisations, as well as government health policy actors, have a responsibility to protect their staff from burnout and stress and enable them to achieve personal growth in times of adversity [ 29 ]. The present research aims to inform organizational policy by identifying personal, organisational and environmental variables acting as risk or protective factors for post-traumatic growth amongst community and mental healthcare staff in the United Kingdom during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout caused by prolonged professional stress can be prevented by helping professionals recognize, comprehend and manage work-related stress with professional supervision as additional support [ 26 ].…”
Section: Introductionmentioning
confidence: 99%